Altered Functional Topological Organization in Type-2 Diabetes Mellitus With and Without Microvascular Complications - Zhang, Dongsheng; Huang, Yang; Gao, Jie; Lei, Yumeng; Ai, Kai; Tang, Min; Yan, Xuejiao; Lei, Xiaoyan; Yang, Zhen; Shao, Zhirong; Zhang, Xiaoling (Frontiers in Neuroscience, 2021)
The microvascular complications can accelerate cognitive impairment of patients with type 2 diabetes (T2DM) and have high impact on the quality of life, but the underlying mechanism is still unclear. The complex network in the human brain is the physiological basis for the information processing and cognitive expression. Therefore, this study explored the relationship between the functional network topological properties and cognitive function in T2DM patients with and without microvascular complications (T2DM-C and T2DM-NC). Sixty-seven T2DM patients and 41 healthy controls (HCs) underwent resting-state functional imaging scanner and neuropsychological assessment. Then, graph theoretical network analysis was performed to explore the global and nodal topological alterations in the functional whole brain networks of the T2DM patients. Correlation analyses were performed to investigate the relationship between the altered topological parameters and cognitive/clinical variables. Compared with the HCs, we found the T2DM-C group exhibited significantly higher Eloc, normalized cluster coefficient (γ), and small-world characteristics (σ), patients with T2DM at different clinical stages (T2DM-C and T2DM-NC) have varying degrees of node properties abnormalities. In addition, compared with T2DM-NC, the occipital cortex, cerebellum and middle temporal gyrus of T2DM-C patients have extensive nodal properties disorders. Some disrupted nodal topological properties were correlated with HbA1c levels and creatinine in T2DM-C patients. This study found that T2DM-C patients displayed more extensive changes at different network topology scales and some disordered network node may be affected by both hyperglycemia and microvascular complications. The visual and cerebellar cortices may be the central vulnerable regions of T2DM-C patients.